(untitled) (Eurasian Journal of Humanities and Social Sciences, 2025)
The development of dialogue is not only the mastery of a certain compositional form of speech, but also an important component of the social and personal formation of the child. Dialogue involves not only communication (intellectual content) and orientation towards one’s own interests, but also taking into account the partner’s point of view, his interests, desires, mood. Children accumulate such experience as a result of cooperative activities (joint creation, drawing, playing team games)